+0  
 
0
268
2
avatar
Is -9 a solution of -2f=9-f I believe it is not, but need to check
Guest Mar 4, 2012
 #1
avatar
0
it is...
-2(-9)=18
9-(-9)=9+9=18
Guest Mar 4, 2012
 #2
avatar
0
actually ur right.

-2f=9-f
then -2f+f=9

-f=9
f= -9
Guest Mar 4, 2012

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.